(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
The article examines photographs produced by the Rockefeller Foundation during health campaigns in Brazil (1930s–1940s), focusing on images of the “bled ones.” This qualitative, archival study identifies them not merely as technical records but as scenes of interpellation that reveal agency, astuteness and self-fashioning of those portrayed. The methodology combines social history, visual analysis, and theoretical approaches from Judith Butler, Saidiya Hartman, Tina Campt, and Jacques Rancière. The discussion shows how these images, although inscribed in a biopolitical logic, display resistances and gestures that escape sanitary control. Results indicate that such photographs establish alternative scenes of appearance, enabling critical readings of the relationship between power, body, and visuality. The conclusion is that, even under coercion, subjectivities emerge that displace the exemplary function of the archive and open gaps for fabulations and alternative histories of epidemics.